The Scale Subverted: the Image of Music in the Fluxus Creations - González-Román, Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2012)
This article focuses on music in the Fluxus environment, understood as the artistic creation which aims towards the conquest of space and exceeds mere sonority, in order to enhance its expression through the action of the interpreter and the use of artifacts. The result of all this was a repertoire of images of great connotative power in the art scene in the sixties.